2019
DOI: 10.14744/semb.2019.67944
|View full text |Cite
|
Sign up to set email alerts
|

The Main Surgical Principles and Techniques In the Management of Primary Hyperparathyroidism

Abstract: B aşta primer hiperparatiroidizm (pHPT) olmak üzere paratiroit hastalıkları için planlanan paratiroidektomi ameliyatlarında başarı oranını arttıran en önemli değişkenler; multidisipliner yaklaşımla doğru tanı konması ve hastalığa uygun cerrahi girişimin yapılmasıdır. Bu bağlamda, başarılı bir paratiroidektomi için paratiroitlerin embriyolojisi ve anatomisi iyi bilinmeli ve özümsenmelidir. [1] Primer hiperparatiroidizm (pHPT)'in tek küratif tedavisi cerrahidir. Paratiroidektomide başarı oranını arttıran en ö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 64 publications
3
50
0
Order By: Relevance
“…Our preoperative 99m Tc-MIBI imaging showed that the degree of visualization of the superior PGs was lower, consistent with previous research (33). This may be due to the effect of hemodynamics, gravity, and a relatively narrow growth area, leading to slower pathological growth in the superior PGs than in the inferior PGs (32). From this perspective, we could select the superior PGs for preservation if a dilemma in selecting PG arises intraoperatively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our preoperative 99m Tc-MIBI imaging showed that the degree of visualization of the superior PGs was lower, consistent with previous research (33). This may be due to the effect of hemodynamics, gravity, and a relatively narrow growth area, leading to slower pathological growth in the superior PGs than in the inferior PGs (32). From this perspective, we could select the superior PGs for preservation if a dilemma in selecting PG arises intraoperatively.…”
Section: Discussionsupporting
confidence: 88%
“…During the embryonic development of PGs, inferior PGs originate from the third pharyngeal pouches, while the superior PGs originate from the fourth pharyngeal pouch. Therefore, the anatomical origins of the superior and inferior PGs differ (31,32), which drew our attention to the difference between the superior and inferior PGs. We found that the superior PGs tended to have a lighter weight, smaller volume, lower PCNA expression, and lower degree of hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases involved a single abnormal parathyroid gland located in an usual neck site, but many of such changes occur in other sites including the thymus gland, the retroesophageal space or the thyroid gland. Sometimes, parathyroid lesions have been reported in the pericardium or soft and adipose tissues of the mediastinum up to the angle of the jaw [3,4]. The differentiation between hyperplasia and adenoma may not be easy even for an experienced surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to detect adenoma with conventional preoperative studies, may result in unsuccessful surgery requiring reoperation, prolonged hypercalcemia, and possible future complications. [ 14 ] For this reason, in selected cases, we use ASVS with the approval of the MEB in order to eliminate the need for a second operation in patients with adenomas whose localization cannot be determined. Although ASVS is an invasive technique, prolonged hypercalcemia, patient stress, and additional costs due to complications of a possible reoperation can be prevented with the meticulous use of ASVS.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the quantity of complex cases increases and the effectiveness of disease management improve. [ 14 , 15 ]…”
Section: Introductionmentioning
confidence: 99%